Comment on "A Calibration‐Free Formulation of the Complementary Relationship of Evaporation for Continental‐Scale Hydrology" by J. Szilagyi et al. Issue 9 (28th April 2021) - Han, Songjun; Tian, Fuqiang
Abstract: Szilagyi et al. (2017) proposed an approach to accommodate Brutsaert's (2015) cubic complementary relationship model by scaling down its independent variable x B . This scaling down approach can work under a condition that x B is larger than its counterparts in the cubic equation, but decreases the performance of the model when x B is smaller than its counterparts. Key Points: Szilagyi et al. used an approach to accommodate Brutsaert's complementary relationship model by scaling down its independent variable x B Scaling down can work under a condition that x B is larger than its counterparts in the cubic equation Scaling down decreases the performance of the model when x B is smaller than its counterparts